Complications after Nd YAG Posterior Capsulotomy - Ali Raza, Ali Raza (Journal of Rawalpindi Medical College, 2007)
Background: To analyse the rate of complications associated with Nd YAG posterior capsulotomy. Methods: This prospective clinical study was conducted in Holy Family Hospital over a six-month period. It included five hundred and fifty patients in out door Eye Department, Holy Family Hospital treated with Nd YAG laser capsulotomy due to posterior capsular opacification after cataract surgery. The complications were noted. Results: There was a transient rise of IOP in 27%, mild anterior uveitis in 7%, pits and cracks in 4%, macular edema in 3% and retinal detachment in 2% cases. Complications were managed accordingly and post YAG visual acuity improved in majority of cases. Conclusions: Nd. YAG is an effective instrument used in non-invasive procedure of capsulotomy in patients who are having gross disturbances of vision such as decreased visual acuity, glare and uniocular diplopia. The posterior capsulotomy does have some serious complications after YAG. One can avoid these complications and get the best results.